The Effect of Training and Use of Information Technology on the Quality of the Financial Statement of Village-Owned Enterprises - Mutia Maulita Anggraeni; Sahmin Noholo; Amir Lukum (AJAR, 2023)
This research aimed to figure out the effect of training and the use of information technology on the quality of the financial statement of village-owned enterprises. This research employed a quantitative descriptive method where the data source of this research was primary data obtained directly from respondents through questionnaires distributed to village-owned enterprises administrators and village officials in Tabongo Subdistrict, Gorontalo Regency. Besides, the total population amounted to 54 people, with a total sample was 30 village-owned enterprises administrators determined by using purposive sampling. The findings denoted that partially, the training variable (X1) had a positive and significant effect on the quality of the financial statement of village-owned enterprises (Y), the use of information technology variable (X2) had no significant effect on the quality of the financial statement of village-owned enterprises (Y). Meanwhile, simultaneously, the training (X1) and the use of information technology (X2) variables had a positive and significant effect on the quality of the financial statement of village-owned enterprises (Y).